Editorial: Developments in cardiac implantable electronic device therapy: how can we improve clinical implementation? - Vamos, Mate; Erath, Julia W.; Benz, Alexander P.; Duray, Gabor Z. (Frontiers in Cardiovascular Medicine, 2023)
GRAPHICAL ABSTRACT CIED, cardiac implantable electronic devices; CRT, cardiac resynchronization therapy; CRT-D, cardiac resynchronization therapy defibrillator; EA, electroanatomical; ICD, implantable cardioverter defibrillator; LBB, left bundle branch; LBBAP, left bundle branch area pacing; LV, left ventricular; LVEF, left ventricular ejection fraction; NT-proBNP, N-terminal pro-B-type natriuretic peptide; MRI, cardiac magnetic resonance imaging; S-ICD, subcutaneous defibrillator.